2004
DOI: 10.7227/jace.10.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Story-Telling? Narratives in the Study of Work-Based Learning

Abstract: This paper1 describes in detail the narrative approach taken in a study of a particular facet of learning in the workplace – how people make sense of change. In unstructured in-depth interviews, employees were encouraged to tell their stories about their organisations, revealing details about the organisational culture and the ways in which this shaped the learning about change taking place within them. The paper shows that narrative analysis is a powerful tool with which to investigate work-based learning. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The range of tools currently available are rich resources for teaching and include reflective journalling, 21,22 practice-based narratives [23][24][25][26] and various sets of resources that use words and illustrations, for instance the resources published by St Luke' s Innovative Resources mentioned earlier in this paper. The rationale for using practice-based narratives, or stories, and card sets are briefly discussed below.…”
Section: Resources For Teachingmentioning
confidence: 99%
“…The range of tools currently available are rich resources for teaching and include reflective journalling, 21,22 practice-based narratives [23][24][25][26] and various sets of resources that use words and illustrations, for instance the resources published by St Luke' s Innovative Resources mentioned earlier in this paper. The rationale for using practice-based narratives, or stories, and card sets are briefly discussed below.…”
Section: Resources For Teachingmentioning
confidence: 99%
“…This process may help support Year 6 students and also forms part of the wider transition story for Year 7 students. Reissner () suggested that sharing each other's “stories” can enable individuals to learn from and adapt to changing roles and relationships (nb: here “story” is defined as a personal account of an experience within a setting, as per Reissner, ). This complex process often involves multiple stories being carried out simultaneously which form part of a longer, ongoing story (Reissner, ).…”
Section: Discussionmentioning
confidence: 99%
“…One can even consider stories as a means to manage change insofar as they organize cultural transformation. Once change occurs, success can be measured by the stories that people will tell (Reissner, 2004).…”
Section: Tablementioning
confidence: 99%
“…In meaningful learning, students generate new meanings, perspectives, and ways of thinking about their professional practice and organizations. It configures a situated, continuous, interactional activity, in which narratives are an inescapable pillar (Reissner, 2004).…”
Section: Typologies Of Educational Strategiesmentioning
confidence: 99%
See 1 more Smart Citation